Competition between Chlamydia psittaci and L cells for host isoleucine pools: a limiting factor in chlamydial multiplication. - Hatch, T P (1975)
L cells (mouse fibroblasts) supported the multiplication of the obligately intracellular parasitic bacterium Chlamydia psittaci (strain 6BC) when incubated in fresh growth medium (medium 199 + 5% fetal calf serum). When incubated in the medium supernatant from a 24-h-old culture of uninfected L cells (24-h used medium), uninfected cells did not divide and infected cells did not provide an adequate environment for the multiplication of C. psittaci, which persisted in a noninfectious latent state within the host cells. The failure of both L cells and chlamydiae to divide resulted from an overall reduction in the rate of protein synthesis by both host and parasite brought about by an insufficiency of the essential amino acid isoleucine in 24-h used medium. The concentration of isoleucine required to activate minimal growth of C. psittaci also minimally stimulated uninfected L cells to divide. The addition of cycloheximide to 24-h used medium also activated the latent chlamydial infection because it stimulated the incorporation of host protein-derived isoleucine into chlamydial protein. The results suggest that the chlamydial parasite and the L-cell host compete for the isoleucine in the soluble pool of the host cell and that the parasite is capable of sequestering isoleucine for its own biosynthetic needs only when the concentration of isoleucine in the host pool rises above the level required to maintain the hose in the stationary state. Extrapolation of the results obtained with the L cell-C. psittaci model system to natural latent chlamydial infections is discussed.